Systematic Review of Game-Based Football Learning for School Students - Nawir, Nukhrawi; Bismar, Ahmad Rum (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This systematic review explores the impact of game-based learning (GBL) methods on football instruction for school students, drawing on 12 peer-reviewed articles published between 2014 and 2024. The review follows PRISMA guidelines and focuses on five key domains: technical skill development, tactical understanding, motivation, physical fitness, and pedagogical implications. The studies reviewed employed models such as Teaching Games for Understanding (TGfU), Small-Sided Games (SSG), and hybrid approaches in primary and secondary school settings. Quantitative findings revealed that GBL significantly improved technical football skills in 83% of the studies. For instance, in a study by Zhai et al. (2023), students participating in SSG-based training improved their passing accuracy by 19% and dribbling performance by 14% over six weeks. In terms of tactical cognition, 75% of the articles reported increased decision-making ability, with García-Ceberino et al. (2020) noting a 23% gain in tactical awareness among middle school students using the TGfU model. Furthermore, 9 out of 12 studies indicated a notable increase in student motivation and engagement. Gil-Arias et al. (2017) recorded a 22% rise in self-reported motivation scores in GBL classrooms. Physical fitness metrics also improved, with studies documenting gains in aerobic capacity and agility. Overall, GBL fosters a student-centred learning environment that enhances cognitive, physical, and affective outcomes in football education. The review underscores the need for structured implementation and further longitudinal research to ensure sustainability and efficacy in diverse educational contexts.